Improving Volunteer Productivity and Retention during Humanitarian Relief Efforts - Lassiter, Kyle; Alwahishie, Abdelwahab; Taaffe, Kevin (International Journal of Supply Chain Management, 2014)
In the aftermath of a disaster, humanitarian organizations quickly assemble a workforce that can immediately serve a communitys needs. However, these needs change over time, and the volunteer base (and their skill sets) also changes over time. In this paper, a mathematical programming model is formulated to solve a volunteer assignment problem in which beneficiaries needs are addressed based on how many volunteers are assigned to each of the levels of needs. In addition, we also examine the changes in these volunteer assignments based on several key cost parameters, need likelihood scenarios, and volunteer training opportunities. Under various demand scenarios, the optimum decision is to begin training some unskilled volunteers early in the response period even when the short-term, unskilled task demands are still high, in preparation for the more skilled, long-term task demands that are yet to come. Humanitarian relief organization managers who generally feel as though a peak of long-term/skilled volunteer task demands will come at some point during the disaster response should strongly consider allowing volunteer training assignments.